COVID-19 in patients on maintenance dialysis in the Paris region (2020)
Introduction: Coronavirus disease 2019 (COVID-19) represents a serious threat to patients on maintenance dialysis. The clinical setting, mortality rate, and prognostic factors in these patients have not been well established. Methods: We included all dialyzed patients with COVID-19 referred to our dialysis center between March 11 and April 11, 2020. Data were obtained through the review of the medical records and were censored at the time of data cutoff, on May 11, 2020. Results: Forty-four patients on maintenance dialysis with COVID-19 were referred to our dialysis unit during the COVID-19 epidemic. Median age was 61 years (interquartile range [IQR]: 51.5–72.5); 65.9% were men. Comorbidities included hypertension (97.7%), diabetes mellitus (50%), and chronic cardiac (38.6%) and respiratory (27.3%) diseases. Initial symptoms were fever (79.5%), shortness of breath (29.5%), cough (43.2%), and diarrhea (13.6%). Three profiles of severity were distinguished based on the World Health Organization (WHO) progression scale. Forty-one (93.2%) were hospitalized and only 3 were maintained on outpatient hemodialysis. Thirty-three (75%) patients required oxygen therapy, including 15 (45.5%) who were referred to the intensive care unit. Overall, 27.3% of patients died, and 58.5% were discharged from hospital, including only 2 (13.3%) of those admitted to the intensive care unit. By multivariate analysis, cough, thrombopenia <120 g/l, lactate dehydrogenase (LDH) level greater than 2 times the upper limit of normal, and blood C-reactive protein (CRP) >175 mg/l were significantly associated with death. Conclusion: A major outbreak of COVID-19 occurred in the Paris region, and spread among dialyzed patients. Our study underscores the severity of COVID-19 in these patients and identified prognostic markers.